ANALISIS KESADARAN, PENYULUHAN WAJIB PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI KPP BATAM SELATAN - Muharram, Denissah; Permata Husda, Anggun (SCIENTIA JOURNAL, 2023)
This study aims to analyze the effect of taxpayer awareness, tax counseling and tax sanctions on taxpayer compliance at KPP Batam Selatan. This study uses a descriptive and quantitative statistical approach with a population of 400,034 WPOP in Batam City and the sample in this study is 100 respondents and uses a questionnaire as a data collection instrument. From data analysis, it was found that taxpayer awareness affects taxpayer compliance with t count (7.309) > t table (1.985), tax counseling affects taxpayer compliance with t count (2.653) > t table (1.985) and tax sanctions affect taxpayer compliance with t count (2.089) > t table (1.985). Simultaneously the results of the F test on taxpayer awareness, tax counseling and tax sanctions affect taxpayer compliance with F count (53.608) > F table (3.09). Keywords: Taxpayer Awareness; Tax Counseling; Taxpayer Compliance; Tax Sanctions.